Effect of NPK Fertilizer and Trichoderma harzianum-Enriched Oil Palm Empty Fruit Bunch Compost on the Growth of Oil Palm Seedlings - Purwanto, Benang; Shalihy, Wildan; Indrawati, Indrawati (Agro Bali : Agricultural Journal, 2025)
Early-stage oil palm seedlings require organic fertilizer as a growth biostimulant to produce healthy seedlings with optimal growth. Providing oil palm empty fruit bunch (OPEFB) compost in a planting medium supplies nutrients, improves the medium, and introduces the biological agent Trichoderma harzianum. The purpose of this study was to analyze how the interaction of NPK fertilizer and T. harzianum-enriched OPEFB compost affected the growth of oil palm seedlings. This study used a factorial Randomized Block Design (RBD) with two treatments: three levels of NPK fertilizer (2.5, 5.0, and 7.5 g. plant-1) and four levels of T. harzianum-enriched OPEFB compost (0, 300, 600, and 900 g. plant-1). The results showed that the interaction of NPK fertilizer and T. harzianum-enriched OPEFB compost only affected root fresh weight, while the independent test revealed that NPK fertilizer affected plant height, number of leaves, and stem diameter. OPEFB compost affected plant height, number of leaves, stem diameter, and shoot fresh weight. The application of NPK 2.5 g. plant-1 and T. harzianum-enriched OPEFB compost at a dose of 300 g. plant-1 independently contributed positively to the growth of oil palm seedlings during the pre-nursery stage, where NPK fertilizer was not needed in large amounts. Additionally, the release of phosphorus (P) and potassium (K) nutrients occurred gradually, making them slowly accessible to plants.